Community Collective Marks: Status, Scope and Rivals in the European Signs Landscape - Dani, Kalliopi (Munich Intellectual Property Law Center - MIPLC, 2014)
This book looks into the nature and status of Community collective marks and explores to what extent they can incorporate certification marks under the current European trade mark law. Welcoming the proposal for a new European Trade Mark Regulation in 2013, the study argues that the two genres should be distinguished from one another, serving distinct purposes. Further, the significance and role of Geographical Indications under the European Union Law are addressed, as well as the question of whether they need to be kept as a separate regime. Although the advantages of each sign are obstructed by discrepancies in terminologies and confusion in legal theory and practice, the author examines the potential of each system by analysing the CTMR as it stands and the OHIM practice, comparing them to national legislations and elucidating the intention of the European legislator.